The relationship between myocardial microstructure and strain in chronic infarcts, assessed using diffusion tensor imaging and feature tracking. (13th July 2021) - Sharrack, N; Das, A; Kelly, C; Aldred, M; Teh, I; Stoeck, CT; Kozerke, S; Chowdhury, A; Jex, N; Ben-Arzi, H; Swoboda, PP; Greenwood, JP; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation Background: Cardiac diffusion tensor imaging (cDTI) is a novel technique for the non-invasive assessment of myocardial microstructure.  It allows in-vivo characterisation of microstructural changes post myocardial infarction (MI). Previously published evidence shows significant loss of sheetlet orientation as derived by cDTI secondary eigenvector (E2A), and loss of subendocardial cardiomyocytes derived by reductions in the proportions of myocytes with right-handed orientation (RHM) on helix angle (HA) maps. The assessment of myocardial strain by feature tracking (FT) allows the measurement of radial strain (RS), thought to be driven by the dynamic reorientation of laminar sheetlets, and longitudinal strain (LS), which is thought to relate to subendocardial function. We sought to explore the relationship between the strain and cDTI parameters in patients at 3 months following ST-elevation MI (STEMI). Methods: Twenty five STEMI patients (M:F = 18:7, mean age 58 ± 9) underwent 3T CMR scan (mean interval 106 ± 17 days) with the following protocol: second order motion compensated (M2), free-breathing spin echo DTI (3 slices, 18 diffusion directions at b-values 100s/mm2, 200s/mm2 and 500s/mm2, acquired resolution was 2.20*2.27*8mm3; cine gradient echo and Late Gadolinium Enhancement (LGE) imaging. HA maps were described by dividing values into left-handed HA (LHM, -90< HA < -30), circumferential HA (CM, -30° < HA < 30°), and right-handed HA (RHM, 30° < HA < 90°) and reported as relative proportions. Segmental analysis were undertaken to derive: HA proportions, E2A, longitudinal strain and LGE%. Segments positive for LGE were classed as infarct segments. Results: cDTI acquisition was successful in all patients (acquisition time 13 ± 5mins). Mean ejection fraction was 47 ± 8% with mean LGE in the infarcted segment of 57 ± 27%. Mean radial strain was 21 (95% confidence interval, 15-26). The mean E2A was 44 (95% confidence interval 41-47). There was a significant correlation between segmental radial strain and segmental E2A in infarcted segments (p < 0.001, figure 1). In addition, segmental longitudinal strain correlated with the proportion of RHM on HA maps (p < 0.02, figure 2). Conclusion: Through the combined use of cDTI and FT in patients with chronic infarcts, our results show that the loss of sheetlet orientation assessed using E2A, correlates with worsening radial strain. Segments with less subendocardial cardiomyocytes, evidenced by a lower proportion of myocytes with right-handed orientation on HA maps, correlated with worse longitudinal strain. While this could potentially elucidate the complex association between myocardial microstructure and regional function, further studies are needed to define the incremental clinical value of cDTI.